Numerical Simulation of Leslie-Gower Predator-Prey Model with Stage-Structure on Predator - Pratiwi, Rima Anissa; Suryanto, Agus; Trisilowati, Trisilowati (The Journal of Experimental Life Science, 2018)
In this paper, we introduce Leslie-Gower predator-prey model with a stage-structure population on the predator. This model consists of two populations, that are prey and predator populations. Here, we divide predator into two stages. Thus, we have three classes of population in this model that are prey, juvenile predator, and mature predator. The focus of this paper is to know the interaction between the population that is affected by stage-structure in predator population in the model and to study numerically the effects of stage-structure in predator population on the interaction of prey and predator. It is found that the transition rate from juvenile to mature predator is a very important parameter which may determine the long-term behavior of both prey and predator.Keywords: Leslie-Gower model, predator-prey model, stage-structure.